2020
DOI: 10.20527/dentino.v5i1.8116
|View full text |Cite
|
Sign up to set email alerts
|

HE EFFECT OF BINJAI LEAVES EXTRACT (Mangifera caesia) ON INCISIONAL BACK WOUND OF MICE (Mus musculus) TO THE NUMBER OF NEUTROPHIL CELLS (Preliminary Study of Drug Preparations for Wound Healing)

Abstract: Background: Ethanol extract of binjai leaves contain bioactive compounds in the form of flavonoid and saponin which is potential as anti-inflammatory, so it will be able to control the wound healing process. Binjai leaves extract can affect the number of neutrophil on inflammatory phase, as it is characterized by neutrophil cells infiltration to the wound tissue, so its number will increase at the beginning of inflammatory phase and decrease on the 3rd day. Objective: To prove the effect of binjai leaves extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…9 The previous research on binjai leaves given topically in the form of extracts has been shown to have an effect on the number of neutrophil cells in the wound healing process. 10 The application of drugs to the skin and mucosa can be more optimal if the extract is made into gel preparation. Gel preparations are medicinal preparations that are often used for topical administration.…”
Section: Introductionmentioning
confidence: 99%
“…9 The previous research on binjai leaves given topically in the form of extracts has been shown to have an effect on the number of neutrophil cells in the wound healing process. 10 The application of drugs to the skin and mucosa can be more optimal if the extract is made into gel preparation. Gel preparations are medicinal preparations that are often used for topical administration.…”
Section: Introductionmentioning
confidence: 99%